Keepin' it real : school success beyond black and white - Carter, Prudence L. (New York ; Oxford : Oxford University Press, 2005)
Prudence Carter investigates why African-American and Latino students perform less well academically than their Asian and white peers and argues that what is needed is a broader recognition of the unique cultural styles and practices that non-white students bring to the classroom.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Multicultural education -- United States; African American students -- Ethnic identity; Hispanic American students -- Ethnic identity; Academic achievement -- Social aspects -- United States